2021
DOI: 10.31018/jans.v13i2.2616
|View full text |Cite
|
Sign up to set email alerts
|

Molecular surveillance of Dengue Virus (DENV) and its co-infection with Chikungunya Virus (CHIKV) among febrile patients: A comparative study from South Delhi, India

Abstract: Dengue and Chikungunya are two major arboviral infections transmitted worldwide by the mosquitoes, Aedes aegypti and Ae. albopictus. India suffers enormously with both Dengue and Chikungunya as they pose a great public health challenge. The present study aims to evaluate the prevalence of Dengue Virus (DENV), Chikungunya Virus (CHIKV) and DENV/CHIKV co-infection (by Reverse-Transcriptase Polymerase Chain Reaction (RT-PCR)/Enzyme Linked Immunosorbent Assay (ELISA), their clinical features, DENV serotypes and CH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…We also observed that in the year preceding 2016 there were reports of DENV-2 and 4 co-circulating which was also the case during 2009-2010 which showed a jump in chikungunya infections post-co-circulation of DENV-2 and 4 ( Table II ). The recent molecular surveillance study during 2017-18 from south Delhi comparing DENV/CHIKV co-infection and DENV mono-infection from 2008 to 2010 detected the high prevalence of CHIKV IgG antibody in 2017-18 and joint pain was particularly present in co-infection cases as compared to DENV mono-infection 113 . These observations prompt us to hypothesize that co-circulation of dengue serotypes may affect the occurrence of other arboviral infections, particularly CHIKV, and warrant detailed epidemiological surveillance of arboviral infections in a locality to understand the transmission dynamics of the infections ( Table II ).…”
Section: Concurrent Dengue Infection With Other Arbovirusesmentioning
confidence: 99%
“…We also observed that in the year preceding 2016 there were reports of DENV-2 and 4 co-circulating which was also the case during 2009-2010 which showed a jump in chikungunya infections post-co-circulation of DENV-2 and 4 ( Table II ). The recent molecular surveillance study during 2017-18 from south Delhi comparing DENV/CHIKV co-infection and DENV mono-infection from 2008 to 2010 detected the high prevalence of CHIKV IgG antibody in 2017-18 and joint pain was particularly present in co-infection cases as compared to DENV mono-infection 113 . These observations prompt us to hypothesize that co-circulation of dengue serotypes may affect the occurrence of other arboviral infections, particularly CHIKV, and warrant detailed epidemiological surveillance of arboviral infections in a locality to understand the transmission dynamics of the infections ( Table II ).…”
Section: Concurrent Dengue Infection With Other Arbovirusesmentioning
confidence: 99%